(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Analysis of literature data indicates the presence of persistent difficulties in the differential diagnosis of pulmonary tuberculosis. The incidence of discrepancies between the primary and established diagnoses in pulmonary tuberculosis, malignant neoplasms of the lungs, pneumonia and sarcoidosis of the respiratory organs ranges from 16.7% to 97.1% [42; 47; 58]. In addition to the fact of establishing an accurate diagnosis for any disease, the timing of its verification also plays a significant role in the prognosis [12].